A geographical perspective on the Aral Sea crisis: three interpretations of an image - White Kristopher D. (Bulletin of Geography. Socio-Economic Series, 2013)
The Aral Sea crisis has gained global notoriety as a human-induced environmental disaster. This paper contextualizes this crisis within a broad geographical framework. Three interpretations of a single photographic image emblematic of the desiccation of the Aral Sea are related to general foci within the academic discipline of geography. These interpretations serve to guide a framing of the Aral Sea crisis within a geographical context. This is presented as a geographical problem, incorporating elements and processes salient to physical geography, human geography, and human-environment interaction. With ecological and societal sustainability in the immediate Aral Sea region still a pressing concern, geographers are well positioned to contribute relevant, research-driven insights.